Avaliação dos procedimentos de boas práticas na área de alimentos e bebidas em hotéis - Serafim, Ana Lúcia (2010)
The hotel industry has grown over the years due to increased tourism in worldwide. In this sector, feeding is a characteristic, because the concept of hosting is inevitably linked to food. But one concern is that not enough provide food to the guests, is necessary give them a food safe from the point of view of sanitary, in accordance with the current legislation. The aim of this study was to verified the procedures for Good Practices in the areas of food and drink (production of meals) in hotels, in Rio Grande do Sul within the context of the FIFA World Cup 2014, as well as check the sample characteristics. From August to October 2010 in a sample of 12 hotels in Porto Alegre, was applied to a form with open and closed questions about the characteristics of the hotels and the respondents. Was realized a hygienic sanitary diagnosis based on the current legislation through visual evaluation and analysis the adopted procedures. It was found that none of the hotels have the presence of a responsible trained technician. There is a lack of knowledge on the part of the responsible about the hygienic sanitary legislation of food, both at federal as state levels, and the hotels do not have implemented good practices. The percentage of general sanitary adequation, of the areas of food and drink in hotels, was classified as level acceptable and insatisfactory. Through the results, it is suggested that establishments seek to achieve improvements, for that the health of the guest and the image of the establishment are not compromised.